Exploring fintech adoption: the role of age, education and ai openness - Varga, Laura; Becsky-Nagy, Patrícia (Economica, 2026)
The aim of this research was to investigate the spread of fintech innovations, particularly digital payment solutions, and the related issues of data protection. Based on the questionnaire survey, it can be concluded that younger generations are more open to innovative fintech solutions, use them more frequently, and are less concerned about potential risks and dangers. In contrast, older age groups exhibit different characteristics. The acceptance of digital solutions increases with the level of education, especially in the case of innovations such as online banking or mobile payments. However, openness to the application of artificial intelligence in finance is still in its infancy, and no significant correlation was found between educational attainment and openness to AI-based financial services. The analysis also placed strong emphasis on issues of security and trust. The results show that while age influences which payment method individuals consider the safest, education level does not have a significant effect on this perception. These findings suggest that attitudes towards innovation are influenced not only by age-related characteristics but also, in some cases, by the level of education. Overall, the research highlights a growing acceptance of digital financial solutions, particularly among young people, but it also emphasizes the ongoing importance of trust—especially from the perspective of older generations and users concerned about data protection.